A continuing mission to optimize the care of older women with breast cancer - Cheung, Kwok-Leung (MDPI, 2017)
The majority of cases of breast cancer occur in the older population who are often un-represented in clinical trials. Given the growing ageing population globally, it becomes urgent and important to identify an optimal approach so that older women with breast cancer are neither under- or over-treated. An inter-disciplinary research program is ongoing to investigate differing tumor biology according to age, and the potential use of a geriatric assessment tool, aiming to help select older women with primary breast cancer for a personalized and optimal treatment. Full considerations of the biology of the patient’s cancer and the geriatric domains of the patient must be taken into account when making treatment decisions.